A Case Study: Visualizing Coulomb Forces With the Aid of Augmented Reality. (December 2019) - Tomara, Marina; Gouscos, Dimitris
In this work, we describe an educational approach based on augmented reality (AR) and mobile technology that has been developed with the aim to engage students in a learning procedure regarding the electric forces as well as Coulomb's Law. Initially, we present the AR learning environment and we explain its design principles with respect to the educational goals we aim to accomplish. The idea behind the present approach has been to present students with a novel learning environment that aligns well with their familiarization with mobile technology and the pleasure they take in making use of this technology, in order to stimulate their intrinsic motivation and learning performance. In addition, we demonstrate the early results of a classroom study performed in order to estimate students' reaction to the AR approach and get an indication of their motivation levels and ease of use, with respect to the AR tool. Based on the study results, we conclude that students have demonstrated positive attitudes toward the AR learning approach and we claim that mobile AR may be incorporated for educational purposes in physics curricula.